Les drive : l'avenir de la grande distribution alimentaire ? Une analyse en termes de valeur perçue du parcours client et du mix marketing/logistique. Issue 1 (2nd January 2021) - Mevel, Olivier; Morvan, Thierry; Morvan, Nélida
ABSTRACT: This paper aims to study drive-in users' satisfaction and expectations concerning a new service formula that comes as a complement to existing services (hypermarkets, supermarkets). We sought to determine the elements of differentiation likely to trigger the emergence of new priorities for retailers who wish to modify the click-and-collect model. We conducted an empirical survey on a sample of 1078 individuals in Brittany and in the "Loire Atlantique" region. Our work identifies the following areas for improvement, as sources of differentiation: the design of the brand's website, the information sent to the user, the range of products on offer and the complementary customised solutions for users.